An Evaluation of Single-Case Reading Intervention Study Quality for Students With and At Risk for Emotional and Behavioral Disorders. (November 2017) - McKenna, John William; Kim, Min Kyung; Shin, Mikyung; Pfannenstiel, Kathleen
Researchers have noted the lack of research to guide reading practice for students with and at risk for emotional and behavioral disorders (EBD). Although comprehensive syntheses have identified promising practices and areas for future research, none have evaluated the rigor of studies according to quality indicators. The current study evaluated the extant single-case reading intervention research for this student population according to the What Works Clearinghouse (WWC) standards. Thirty studies met article selection criteria, 20 (66.6%) of which had at least one dependent variable that did not meet design standards. Study findings suggest a need for researchers to employ stronger designs and place a greater emphasis on investigating the effects of reading instructional practices in inclusive settings. Overall, two reading interventions were identified as potentially promising: cognitive mapping and a listening while reading accommodation. Furthermore, findings suggest that it may be advantageous to embed behavioral strategies within reading interventions. Study limitations include the exclusive use of single-case design studies and a reliance on visual analysis to determine intervention effectiveness.